CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY TEST OF HONEY, LEMON, GINGER FERMENTATION AGAINST BACTERIA CAUSING ACUTE RESPIRATORY INFECTIONS (ARI) - Andi Dian Astriani; Muhammad Iqbal (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Acute respiratory infection (ARI) is a disease that attacks one or more parts of the airway, from the nose to the alveoli. The most common bacteria found in the samples of patients with ARI were Streptococcus pneumonia, Staphylococcus aureus, and Klebisilia pneumonia. Honey contains flavonoids, amino acids and potassium as antibiotics that are bactericidal (kill bacteria) and bacteriostatic (inhibit bacterial growth). Gingerol in ginger (Zingiber officinale) and lemon (Citrus limon) has antibacterial activity. Honey fermentation is believed to have great potential as an antibacterial compound. This study aimed to determine the inhibitory activity and physical characteristics of fermented honey, lemons, and ginger against ARI bacteria. The test bacteria used were Streptococus pneumonia, Stahpylococcus aureus, and Klebsilia pneumonia. Fermentation of honey, lemon, and ginger was performed with variations in fermentation time (days 1, 3, 5, and 7) and honey without fermentation to determine the effect of fermentation time on inhibitory activity. The inhibition activity was tested using the agar diffusion method. Measurement of inhibition diameter using a caliper. Determination of ginger lemon fermented honey characteristics, including water content, sucrose content, and total sugar content, using gravimetric and titrimetric methods. Based on the activity test, honey fermented for 1 day had the greatest inhibitory activity of 9.71 mm; 9.20 mm; and 9.86 mm against Stahpylococcus aureus, Staphylococcus pneumonia, Klebsilia pneumonia compared to honey fermented for 3 days, 5 days, 7 days and honey without fermentation. ...